2023
DOI: 10.1002/jbt.23414
|View full text |Cite
|
Sign up to set email alerts
|

Buspirone attenuated methotrexate‐induced hippocampal toxicity in rats by regulating Nrf2/HO‐1, PPAR‐γ, NF‐κB/nNOS, and ROS/NLRP3/caspase‐1 signaling pathways

Abstract: Methotrexate (MTX) is a chemotherapeutic agent widely used to treat a variety of tumors. Nonetheless, MTX‐induced hippocampal neurotoxicity is a well‐defined dose‐limiting adverse effect that limits clinical utility. Proinflammatory cytokine production and oxidative stress are possible mechanisms for MTX‐induced neurotoxicity. Buspirone (BSP), a partial agonist of the 5‐HT1a receptor (5‐HT1aR), has emerged as an anxiolytic drug. BSP has been shown to possess antioxidant and anti‐inflammatory effects. The curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…Cell experiments have found that PPARγ, as a potential drug target for treating neurodegenerative diseases, chiefly mediates the anti-inflammatory, anti-Aβ, anti-apoptotic and anti-oxidant effects [ 14 , 15 ]. In terms of anti-inflammation, PPARγ is expressed in both monocytes and macrophages, which, after activation, inhibits monocytes or macrophages from producing inflammatory mediators IL-1β, IL-6, TNF-α, as well as inducible nitric oxide synthase [ 16 ]. PPARγ inhibits the proinflammatory gene expressions at the transcriptional level by antagonizing the activities of transcription factors like NF-κB, AP-1 and STAT1 [ 17 ], and its agonists can effectively inhibit the inflammatory molecule production mediated by microglia and astrocytes in the central nervous system [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cell experiments have found that PPARγ, as a potential drug target for treating neurodegenerative diseases, chiefly mediates the anti-inflammatory, anti-Aβ, anti-apoptotic and anti-oxidant effects [ 14 , 15 ]. In terms of anti-inflammation, PPARγ is expressed in both monocytes and macrophages, which, after activation, inhibits monocytes or macrophages from producing inflammatory mediators IL-1β, IL-6, TNF-α, as well as inducible nitric oxide synthase [ 16 ]. PPARγ inhibits the proinflammatory gene expressions at the transcriptional level by antagonizing the activities of transcription factors like NF-κB, AP-1 and STAT1 [ 17 ], and its agonists can effectively inhibit the inflammatory molecule production mediated by microglia and astrocytes in the central nervous system [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%